2015
DOI: 10.1177/0363546515579179
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Coracoclavicular Ligament Reconstruction With a Flip-Button Technique (MINAR)

Abstract: The MINAR technique is a safe procedure and achieves good to excellent clinical and radiographic results in the surgical treatment of high-grade AC joint dislocations. Despite the simplicity of this technique, the surgeon has to overcome the learning curve to minimize the risk of recurrent dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
6
37
0
5
Order By: Relevance
“…Present study showed, that mini-open operative ACLC treatment was required in 21.5 % of acute ACJ dislocations to achieve anatomical reduction. This finding might at least partly explain the high rates of horizontal ACJ instability following closed techniques of acute ACJ reconstruction [13, 17, 24, 28, 30, 33]. Additional operative ACLC repair might support anatomical ACLC healing, if sufficient biomechanical augmentation is provided during the phase of healing [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present study showed, that mini-open operative ACLC treatment was required in 21.5 % of acute ACJ dislocations to achieve anatomical reduction. This finding might at least partly explain the high rates of horizontal ACJ instability following closed techniques of acute ACJ reconstruction [13, 17, 24, 28, 30, 33]. Additional operative ACLC repair might support anatomical ACLC healing, if sufficient biomechanical augmentation is provided during the phase of healing [10].…”
Section: Discussionmentioning
confidence: 99%
“…The superior ACLC functions as the major horizontal stabilizer of the ACJ [3, 5, 8, 16]. Insufficient superior ACLC healing may contribute to persistent horizontal ACJ instability, which is reported in up to 50 % of cases following both arthroscopic and open reconstruction of acute ACJ dislocations [13, 17, 24, 33]. Horizontal ACJ instability represents a clinically relevant issue, since several studies showed an association with inferior functional outcome [13, 19, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Rosslenbroich and colleagues [16] observed a good clinical outcome regarding 96 patients who had undergone AC reconstruction with a fixation button (Fliptack).…”
Section: Discussionmentioning
confidence: 99%
“…Acromioclavicular joint (ACJ) dislocation is a common injury among young people between 20 and 40 years old who practice sports, and it has an incidence of between 9% and 17% of all shoulder injuries [1][2][3][4][5][6]. The pattern of this trauma is a direct force to the acromion with the arm in an adducted position [7].…”
Section: Introductionmentioning
confidence: 99%